2019
DOI: 10.3390/su11226209
|View full text |Cite
|
Sign up to set email alerts
|

Location-Based Tracking Data and Customer Movement Pattern Analysis for Sustainable Fashion Business

Abstract: Retailers need accurate movement pattern analysis of human-tracking data to maximize the space performance of their stores and to improve the sustainability of their business. However, researchers struggle to precisely measure customers’ movement patterns and their relationships with sales. In this research, we adopt indoor positioning technology, including wireless sensor devices and fingerprinting techniques, to track customers’ movement patterns in a fashion retail store over four months. Specifically, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Figure 11 illustrates the ISTSM matrix of the six indoor semantic trajectories and the dendrogram resulting from the agglomerative hierarchical clustering with the ISTSM. In Figure 11, the cell value of the grid is the ISTSM value, and the numbers (3,6,1,2,4,5) on the left and top of the grid are the IDs of the six trajectories. The dendrogram is on top of the grid.…”
Section: Trajectory Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 11 illustrates the ISTSM matrix of the six indoor semantic trajectories and the dendrogram resulting from the agglomerative hierarchical clustering with the ISTSM. In Figure 11, the cell value of the grid is the ISTSM value, and the numbers (3,6,1,2,4,5) on the left and top of the grid are the IDs of the six trajectories. The dendrogram is on top of the grid.…”
Section: Trajectory Comparisonmentioning
confidence: 99%
“…Indoor positioning devices, such as WiFi, Bluetooth, and RFID (radio frequency identification) devices, generate an extensive number of indoor trajectories for objects moving indoors. With indoor trajectories, insightful indoor movement patterns reflecting complex human spatial behavior can be discovered by adopting various methods, such as clustering analysis [1][2][3][4]. These methods are frequently based on an indoor trajectory similarity that measures the similarity degree of two indoor trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [51] combined questionnaire data about customers' purchasing behavior and their movement trajectories tracked by the UWB indoor positioning system, and found that the spatial layout of the supermarket significantly affect people's impulse purchasing behavior. Kim et al [52] conducted three field experiments with different visual merchandising displays in shopping mall to compare customer movement patterns based on location-based tracking data. Their results confirmed that effective store rearrangement could change customer movement patterns and improve the overall sales of store zones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the influencing factors were quantified via a linear multivariable regression model, where customer flow density on the weekend was the dependent variable and the independent variables included locational and social factors. To determine the factors that may influence customer flows to stores, we needed to choose the influencing factor first, which was based on previous research [3,4,13,14,18,50,52] and online comment information (dianping.com). Here, we selected 9 factors, among which the first eight were locational variables and the last one was a social one.…”
Section: Analysis Proceduresmentioning
confidence: 99%
“…The fifth paper, with the title "Location-Based Tracking Data and Customer Movement Pattern Analysis for Sustainable Fashion Business" [5], provides results that might be useful for managers trying to improve the sustainability of their businesses. It describes three field experiments with different visual merchandising displays in stores in a shopping mall in South Korea to analyse customer movement patterns based on indoor location-based tracking data.…”
mentioning
confidence: 99%